48. OUTCOMES OF ENDOVASCULAR TREATMENT IN PATIENTS WITH CHRONIC OCCLUSIVE AORTOILIAC ARTERY DISEASE (Vietnam Journal of Community Medicine, 2024)
Background: Incidence of chronic arterial occlusive disease in lower limbs is high in elder patients. Patients’ s chief complains are intermittent claudication, foot ulcer or even systemic sepsis. Typically, treatment of chronic arterial disease in lower limbs is arterial bypass surgery, endarterectomy. However, these are invasive surgeries, requiring general or spinal anesthesia. Recently, endovascular intervention techniques are applied to the treatment with benefits such as: local anesthesia, fewer complications, and feasible to elder patients with severe compromised disease.Objective: To determine the efficacy of, results of endovascular treatment in patients with symptomatic chronic aortoiliac occlusive disease.Methods: From June 2020 to April 2022, the prospective study was carried out on 56 cases with chronic aortoiliac occlusive disease, treated by PTA in Cardiovascular and Thoracic Department, Thong Nhat hospital.Results: Majority of lesions belong to TASC II C (23%) and D (51%). The artery lesions included simple aortoiliac artery (23%), aortoiliac combined with femoropopliteal and/ or infrapopliteal artery (77%). The ankle- brachial index before and after the intervention is respectively 0.43 ± 0.3 and 0.76 ± 0.29 (p
Keywords: peripheral artery disease; aortoiliac occlusive disease; chronic arterial occlusive disease